Safinamide: A Review in Parkinson’s Disease - Blair, Hannah A.; Dhillon, Sohita (CNS drugs, 2017)
Safinamide (Xadago ® ) is an orally active, selective, reversible monoamine oxidase-B inhibitor with both dopaminergic and non-dopaminergic (glutamatergic) properties. In the EU, safinamide is approved for the treatment of mid- to late-stage fluctuating Parkinson’s disease (PD) as add-on therapy to a stable dose of levodopa alone or in combination with other PD medications. Safinamide 50–100 mg/day administered as a fixed or flexible dose significantly increased daily ‘on’ time without dyskinesia (primary endpoint) in patients with mid- to late-stage PD with motor fluctuations in 24-week, placebo-controlled clinical trials. Other outcomes, including motor function, overall clinical status and health-related quality of life, were also generally improved with safinamide. Furthermore, in an 18-month extension of one study, although dyskinesia (primary endpoint) was not significantly improved with safinamide relative to placebo, treatment benefits in other outcomes were generally sustained over 24 months of treatment. Safinamide was generally well tolerated in clinical trials; dyskinesia was the most common adverse event. Although further studies are needed, including comparative and long-term studies, current evidence indicates that safinamide extends the treatment options available for use as add-on therapy to levodopa and other PD medications in patients with mid- to late-stage PD experiencing motor fluctuations.